The Vietnam-United States Comprehensive Strategic Partnership in the Indo-Pacific Region - Manurung, Riski Hasanah (Global and Policy Journal of International Relations, 2024)
The current bilateral relationship between Vietnam and the United States has reached the status of a Comprehensive Strategic Partnership. The evolving cooperation between these two nations is crucial in maintaining stability and promoting growth in the Indo-Pacific region. This study analyzes the dynamics of their cooperation, particularly in economics, politics, and regional security. The study uses the concept of regionalism to analyze the interactions and cooperation in the region, considering the influence of the principles of regionalism on the formation and implementation of the Comprehensive Strategic Partnership. The research methodology is qualitative, using a descriptive-analytical approach. The research identifies and analyses how the Comprehensive Strategic Partnership between Vietnam and the United States affects the Indo-Pacific region's economic, political, and security dynamics. The findings of this research indicate that the Comprehensive Strategic Partnership between Vietnam and the United States plays a crucial role in shaping the Indo-Pacific region's economic, political, and security dynamics. The findings are expected to significantly contribute to the theoretical and practical understanding of the Vietnam-United States regional cooperation and its impact on the region's geopolitical dynamics.Keywords: Comprehensive Strategic Partnership, Indo-Pacific Region, Regional SecurityHubungan bilateral Vietnam dan Amerika Serikat saat ini telah mencapai status Kemitraan Strategis Komprehensif. Kerja sama yang terus berkembang di antara kedua negara ini memegang peran penting dalam menjaga stabilitas dan mendorong pertumbuhan di kawasan Indo-Pasifik. Fokus utama penelitian ini adalah menganalisis dinamika hubungan kerja sama keduannya, khususnya dalam aspek diplomasi, ekonomi, dan keamanan regional. Penelitian ini menggunakan konsep regionalisme untuk menganalisis interaksi dan kerjasama di kawasan, dengan mempertimbangkan pengaruh prinsip-prinsip regionalisme terhadap pembentukan dan pelaksanaan Kemitraan Strategis Komprehensif. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan analisis deskriptif. Penelitian ini mengidentifikasi dan menganalisis bagaimana kemitraan strategis komprehensif antara Vietnam dan Amerika Serikat memengaruhi dinamika ekonomi, politik, dan keamanan di Kawasan Indo-Pasifik. Hasil penelitian ini menunjukkan bahwa kemitraan strategis komprehensif antara Vietnam dan Amerika Serikat memainkan peran yang sangat penting dalam membentuk dinamika ekonomi, politik, dan keamanan di Kawasan Indo-Pasifik. Hasil penelitian ini diharapkan dapat memberikan kontribusi signifikan terhadap pemahaman teoritis dan praktis tentang kerjasama regional Vietnam-Amerika Serikat dan implikasinya dalam dinamika geopolitik kawasan tersebut.Kata-Kata kunci: Kemitraan Strategis Komprehensif, Kawasan Indo-Pasifik, Keamanan RegionalDOI: https://doi.org/10.33005/jgp.v12i01.4301